Josef Strzygowski (1861–1942), Dmitry Ainalov (1862–1939) and the Question of Geographical Borders in the Theory of Art: The Possibility of a “Geographic Eye” - Leonelli, Francesco (Actual Problems of Theory and History of Art, 2020)
Cyril Mango in his book “Byzantium. The Empire of New Rome” (1980), wrote that Byzantineart, along with Byzantine studies, flourished as a prolific ally more in Russia than anywhere else in the world. In contrast, the theory of art in Western European countries branded as derogatory for many centuries the typical iconographical and stylistic features of Byzantine art with the geographically-based stigma “maniera greca” (Greek Manner). This definition often compromised, with some rare exceptions, a correct appreciation of Byzantine and Eastern art in Europe, minimizing the contribution of the East to the development of art in western civilizations. An exception, and a break with this misconception of the Byzantine component of western art, is the controversial essay by the Austrian art historian Josef Strzygowski “Orient oder Rom”(1901). In his study, Strzygowski radically opposes the Rome-based aesthetical theories, such as the widely accepted ideas of Franz Wickhoff and Alois Riegl, surprisingly finding the roots of German and Slavic art in Iran, Armenia and Egypt. The theories of Strzygowski, although connoted from anti-Roman resentment and strong German nationalism, gave a fundamental impulse to the revaluation of Eastern art in Europe. Indeed the ideas of Strzygowski are not very new. In 1890, during a sort of Eastern Grand Tour, he attended the Russian Archeological Congress where he met the Russian scholar Dmitry Ainalov. In 1900 (one year before “Orient oder Rom”), Ainalov published the essay “The Hellenistic Origins of Byzantine Art”, in which he emphasizes the originality of Byzantine art as a Hellenistic product and claims its independency from Roman art. These ideas, which were shared by the Russian scholarship and tended to see patriotically Byzantine art in its uniqueness, helped paradoxically through the mediation of the radical ideas of Strzygowski European scholars to be able to “break down the borders” and develop a better comprehension of the importance of the East. The case of Strzygowski–Ainalov is an example of a typical attempt by the History of Art to evaluate an art object as a pure expression of the spirit of a population and of a particular geographical area. From this initial situation, the paper intends to examine the fundamental contribution of the geography of art to the formation of art theories. To paraphrase Michael Baxandall and his famous “Period Eye”, can we speak of a “Geographic Eye” when we try to comprehend an art period? To what extent is a Geography of Artpossible today? What are the roles of geographical features and borders in the analysis of an art work? What is meant with the geographical definitions (such as “German”, “Italian”, Russian”, or “Western” and “Eastern”) once they are applied to art? In the light of the recent debates on the possibility of a global art history, as well as the developing of new geopolitical horizons, do we have the same conception of the Geography of Art today as the scholars of the past? What are the advantages and the risks of a methodology based on a geographic parameter in considering an art object or an art period?